STRUCTURE OF PEDAGOGICAL CURRICULA PRIMARY EDUCATION DEPARTMENT OF GREECE (Pedagogy of Higher and Secondary Education, 2022)
In the article of Korotkova Yuliya “The structure of the plans of the pedagogical departments for the preparation of primary school teachers in Greece” the structure of curriculums, types of disciplines of 9 pedagogical university departments for the preparation of primary-school teachers are discussed.